'Le goût du jeu (a taste for the game):' pedagogical play, competition, and resistance to neoliberal capitalism in Nathalie Kuperman's Nous étions des êtres vivants. (2nd January 2020) - Fronsman-Cecil, Dorthea Margery
ABSTRACT: This paper proposes to contribute to existing scholarship examining the contemporary French workplace novel by offering a critical reading of Nathalie Kuperman's 2010 novel Nous étions des êtres vivants . In my article, I respond to prior articles addressing the novel as a dissection of political discourse and an entry within the growing corpus of French 'sociological' fiction on work by analysing the novel's metaphors of 'jeu(x) and jouer' ('play(s)' and 'gambling'). I argue that the novel accomplishes its axiological task of opposition to neoliberalism and reactionary discourses on work by deploying a leitmotiv of 'jeux'/'jouer' as a rhetorical strategy. By juxtaposing the novel's representation of work, play, competition, and the 'game of corporate business' in the neoliberal workforce with the radical political philosophies of work and play as avenues for emancipation that were popular in France's past revolts, I bring into relief the historical and ideological criticisms that this 'morality play' set in the metonymic space of a corporate office suggests. In doing so, I show how Kuperman's work invokes radical psychological, pedagogical, and philosophical theories of liberation by representing work and/as play, and more crucially, play at work.